2013
DOI: 10.1002/gps.3987
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of a stepped care programme to prevent depression and anxiety in residents in homes for the older people: a randomised controlled trial

Abstract: A stepped care programme to prevent depression and anxiety in older people living in elderly homes was not considered cost-effective in comparison with usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] minor or sub-threshold depression, [39][40][41][42] depression and anxiety in residential care homes, [43][44][45][46][47] suicidal ideation, 48 alcohol abuse, 49,50 behavioural symptoms in Alzheimer, 51 and mental problems in specific patient groups. 15,[52][53][54][55][56] Evidence showed that the collaborative care strategy is best adapted for the organisation of MHCE, often combined with one of the other operational strategies (see Table 1).…”
Section: Operational Strategiesmentioning
confidence: 99%
“…One concern of a multi-component approach is that it may be more costly than drug therapy or a singular approach (Bosmans et al, 2013). A multi-component approach may require more training of interventionists and more treatment sessions to facilitate delivery of all treatment components.…”
Section: Discussionmentioning
confidence: 99%
“…As with the GDS, the CES-D tended to be used as an outcome measure (Anstey, et al, 2007;Bosmans, et al, 2013) of depression and usually as just one of multiple measurements of mental health and quality of life among older people (Konnert, et al, 2009). Two studies by the same authors also used the scale as an indicator of anxiety in this population (Dozeman, et al, 2012;Dozeman, et al, 2011).…”
Section: Measuring Depressionmentioning
confidence: 99%
“…Just three of the studies used a standardised measure to assess risk of self-harm or suicidal behaviorr directly (Arvanti, et al, 2005;Bosmans, et al, 2013;Dozeman, et al, 2012). Arvaniti et al (2005) used a Greek version of a short diagnostic tool, the Mini International Neuropsychiatric Interview (MINI; Sheehan, et al, 1998) to assess the existence of suicidality based on DSM-IV and ICD-10 criteria as part of their prevalence study comparing community dwelling and residential care home older people.…”
Section: Measuring Self-harm and Suicidal Behaviormentioning
confidence: 99%